PENGARUH MANAJEMEN PASOKAN STRATEGIS TERHADAP KINERJA PERUSAHAAN DENGAN PERAN MEDIASI MOBILISASI SUMBER DAYA BASIS PASOKAN DAN MOBILISASI SUMBER DAYA PASOKAN PASAR - Desca Fortuna; Wahyuningsih Santosa; Gatri Lunarindiah; Muhammad Aditiya (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the influence of strategic supply management on operational performance, with the mediating rolesof supply base resource mobilization and supply market resource mobilization. The research employs a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to employees and managers of manufacturing companies in Indonesia. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that strategic supply management has a positive and direct effect on supply base resource mobilization, supply market resource mobilization, and operational performance. Furthermore, it was found that supply base resource mobilization and supply market resource mobilization mediate the relationship between strategic supply management and operational performance. This study emphasizes the importance of managing supply strategically and the company's ability tomobilize external resources to enhance sustainable operational performance.